EFFECT OF PROFITABILITY, BUSINESS SIZE, AND INSTITUTIONAL OWNERSHIP ON BUSINESS VALUE WITH CAPITAL STRUCTURE AS A MODERATING VARIABLE (Empirical Study on Food and Beverage Companies Listed on The Indonesia Stock Exchange for The 2017-2020 Period) - Arifin, Atwal; Fauziah, Siti; Suwarno, Agus Endro (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to analyze the effect of profitability, business size, and institutional ownership on business value with capital structure as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020. Using purposive sampling, 48 companies were selected as the sample. Multiple regression analysis with IBM SPSS Statistics 25 was employed to analyze the data. The analysis unveiled that profitability affected business value. However, business size had no influence on business value, and institutional ownership did not significantly impact business value. Moreover, the capital structure could moderate profitability with business value but could not moderate business size and institutional ownership.